Virtual Linguistic Landscape During Post-Covid 19 in Haneda Airport Public Space - Putri, Indika; Nurjaleka, Lisda; Afifah, Muthi (Journal of Language and Literature, 2024)
The virtual linguistic landscape was a study that investigated texts that existed in the public space and were done virtually. Haneda Airport had a policy of creating linguistic landscape signs for visitors during the post-COVID-19 situation. This study aimed to examine the use of language, actors, and categories of linguistic landscape signs. There were 888 landscape linguistic signs as the objects in this study. The data was taken with screenshots of sign images from a Haneda Airport-related video uploaded on YouTube. The collection methods were done by using the techniques of observation and documentation. This study used a qualitative descriptive method by applying the linguistic landscape theory of Landry and Bourhis. The result showed that multilingualism with the composition of Japanese-English-Chinese Korean was widely used in the linguistic landscape of Haneda Airport’s public space. Meanwhile, the category of public signs dominates the linguistic landscape signs, keeping with Haneda Airport’s status as a public space. Airport public authorities (top-down) often made public signs and place names using multilingual and bilingual. In contrast, private actors (bottom-up) mostly make commercial shop signs and advertising billboards using monolinguals.